(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
تم تحضير ثلاثة مركبات عضوية فوسفورية تحتوي الجسر =P(S)-NH-P(S)= مع متبادلات الفينيل (PhO) , (Ph) متماثلة وغير متماثلة لاستخدامها كمواد مستخلصة لعنصر البلاديوم وفقاً لطريقة الاستخلاص ( السائل – السائل ) ذات الأهمية الكبرى في استخلاص المعادن النبيلة وعناصر الأتربة النادرة، وحُددت بعض خواصها الفيزيائية والكيميائية ( درجة الانصهار , طيوف UV , طيوف IR ) . اعتُمدت الطريقة الفوتومترية لتحديد تراكيز أيونات معدن البلاديوم في الوسط المائي استُخدم محلول 2- نتروزو,1- نفتول لتحديد التراكيز وحُسبت قيم تراكيزه في الطور العضوي اعتماداً على الفرق بين التراكيز البدائية المحضرة له في الوسط المائي والتراكيز النهائية بعد عملية الاستخلاص . دُرس عامل توزع أيون البلاديوم DPd بين وسط مائي من محلول حمض كلور الماء ووسط عضوي يحتوي تراكيزاً مختلفة من المركبات الفوسفورية العضوية المحضرة سابقاً ، كما دُرس توزع أيون البلاديوم بدلالة تغير قيم الـpH عند تركيزٍ ثابتٍ من المستخلص المستخدم المذكور سابقاً وقُيمت معلومات التوزع رقمياً و بيانياً . Three organic phosphorous compounds containing bridge = P(S)-NH-P(S) = with , (PhO) , (Ph) acting noble metals and rare earth elements, and identified some of the chemical and physical properties (melting point, spectra UV , IR ) . Photometric method adopted to determine the concentrations, as it used the solution of 2-Nitroso, 1- Naphthol to determine the concentrations of palladium ion in the aqueous phase after extraction and its concentrations in the organic phase based on the difference between the concentrations of primitive prepared and the final concentrations. Distribution Ratio DPd was studied of the ion palladium between the aqueous medium of the acid solution of hydrochloric and central Organic Dilutions containing different concentrations of the previous prepared organo phosphorus compounds also was studied the Distribution Ratio DPd of ion palladium depending of changing of pH-values in aqueous medium and central organic Includes fixed concentration from the previous prepared organo phosphorus compounds and evaluated the distribution of information focus numerically and graphically .